Okoljska škoda in njena povrnitev - Lutman, Karmen (Pravni letopis, 2022)
Due to the growing concern for the environment and in promoting the goals of sustainable development, mechanisms for the prevention and remediation of environmental damage are gaining increasing importance. In Slovenian law, measures related to environmental damage are in the domain of administrative law, while private law has a rather limited role in environmental protection. Environmental damage is not legally recognized in Slovenian tort law. However, comparative trends show that private law can have a complementary function in achieving more environmentally friendly practices and in slowing down of climate change. The author discusses some of these practices from abroad, especially in French law, which introduced the concept of civil liability for environmental damage in the Civil Code. The article furthermore analyses the growing trend of climate change litigation in horizontal relationships.
Keywords: deliktno pravo; klimatske spremembe; odškodnina; okoljska odgovornost; okoljska škoda; podnebne tožbe; pravo varstva okolja; trajnostni razvoj; varstvo okolja